Assessing Aging in Reinforced Concrete Using Novel Remote Sensing Techniques - Christofe, Andreas; Danezis, Chris; Hadjimitsis, Diofantos G. (My University, 2020)
Concrete sets, hardens, gains strength, and exhibits reduced permeability over time, but it is not time alone that causes these effects. Most concrete types are confronted with potential deteriorative service conditions that aggravate their properties irrespective of their age. Thus, there is a critical need to develop an appropriate test method to evaluate and identify concrete aging conditions in various structural components. In recent years, many researchers used hyperspectral technology as a nondestructive test method for assessing properties of concrete structures both in the laboratory and in-situ. The purpose of this paper is to present the results of laboratory research using hyperspectral technology to assess aging in concrete. In this test method, several controlled experiments have been carried out in a controlled environment to retrieve the spectral characteristics of concrete samples due to their exposure in an aggressive sodium chloride environment. The results indicate that spectroscopy can be successfully used as a nondestructive test method for the assessment of reinforced concrete aging.
Keywords: Hyperspectral; Spectroscopy; Reflectance; Spectral signature